Conflict Resolution Strategy In Handover Management For 4G And 5G Networks - Abdulraqeb Alhammadi; Wan Haslina Hassan; Ayman A. El-Saleh; Ibraheem Shayea; Yousef Ibrahim Daradkeh; Hafizal Mohamad (Tech Science Press, 2024)
Indexed by WOS/Scopus/ERA